High-temperature optima phosphatases from the cold-tolerant Arctic fungus Penicillium citrinum - Puja Gawas-Sakhalkar; Shiv Mohan Singh; Simantini Naik; Rasik Ravindra (Polar Research, 2012)
Fifty-six fungal isolates from Arctic soils were subjected to primary screening for their ability to solubilize insoluble inorganic phosphate. Nine of the isolates were further analysed quantitatively for phosphatase production using para-nitrophenylphosphate as substrate. Amongst these, a cold-tolerant fungus, Penicillium citrinum strain PG162 was found to be the best producer of intracellular acid phosphatase. Further characterization of the enzyme showed that it is most active in the temperature range of 40–60°C and pH range of 4.2–4.8. The dried enzyme extract is stable at a temperature of up to 50°C for at least 1 h. Its activity is affected by presence of metal ions. Sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS–PAGE) analysis suggests the molecular weight of the enzyme to be between 20 and 29 kDa. The present study is important with respect to our understanding of the kind of enzymatic reactions that take place in the polar microbes, and the extent to which their activity is sustained.